Robotech visual archive : the Macross saga. - Harmony Gold U.S.A. (Firm) (Richmond Hill, Ontario : UDON, 2017)
Robotech is a sweeping science-fiction anime epic in which humans use a vast arsenal of transforming robotic mecha to defend the Earth against alien domination. The franchise has captivated fans for over 30 years, and is widely credited with popularizing anime around the world. This is the ultimate collection of artwork gathered from Robotech's first and beloved era, The Macross Saga. Included in this epic tome are mecha designs, character artwork, pre-production concepts, key art, storyboards, a full episode guide, and more!
"Harmony Gold"-- Cover.
Keywords: Robotech (Television program) -- Pictorial works; Animated television programs -- Pictorial works; Anime -- Pictorial works